Enhancing the Effectiveness of Diabetes Self-Management Education: The Diabetes Literacy Project - Van den Broucke, S.; Van der Zanden, G.; Chang, P.; Doyle, G.; Levin, D.; Pelikan, J.; Schillinger, D.; Schwarz, P.; Sørensen, K.; Yardley, L.; Riemenschneider, H. (Hormone and Metabolic Research, 2014)
Patient empowerment through self-management education is central to improving the quality of diabetes care and preventing Type 2 Diabetes. Although national programs exist, there is no EU-wide strategy for diabetes self-management education, and patients with limited literacy face barriers to effective self-management. The Diabetes Literacy project, initiated with the support of the European Commission, aims to fill this gap. The project investigates the effectiveness of diabetes self-management education, targeting people with or at risk of Type 2 Diabetes in the 28 EU Member States, as part of a comprehensive EU-wide diabetes strategy. National diabetes strategies in the EU, US, Taiwan, and Israel are compared, and diabetes self-management programs inventorized. The costs of the diabetes care pathway are assessed on a per person basis at national level. A comparison is made of the (cost)-effectiveness of different methods for diabetes self-management support, and the moderating role of health literacy, organization of the health services, and implementation fidelity of education programs are considered. Web-based materials are developed and evaluated by randomized trials to evaluate if interactive internet delivery can enhance self-management support for people with lower levels of health literacy. The 3-year project started in December 2012. Several literature reviews have been produced and protocol development and research design are in the final stages. Primary and secondary data collection and analysis take place in 2014. The results will inform policy decisions on improving the prevention, treatment, and care for persons with diabetes across literacy levels.
Keywords: type 2 diabetes; diabetes self-management; health literacy; implementation fidelity; patient level costs of T2D